Linguistic Landscape of a Modern Post-Soviet Capital — Case of Chișinău, Republic of Moldova - Palágyi, A.; Vasiliev, A. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
The study of linguistic landscape considers the hierarchy of languages motivated by political, administrative, and economic reasons, as reflected in the graphic design and order of inscriptions. In this research, we will present the linguistic landscape of Chișinău by analyzing top-down and bottom-up signs and commercial billboards. The choice fell on this city because it is multiethnic, home for Moldovans/Romanians and other nationalities. The relevance of the topic is explained by the fact that Moldova aspires to join the European Union, and in 2018 Chișinău became one of the country’s pilot municipalities for the application of the European Charter for Regional or Minority Languages, which the country has adopted, but has not yet ratified. The new signs must indicate direction to public and cultural institutions, monuments and memorials, parks and major streets, university buildings, the railway station, and the airport with trilingual inscriptions in Moldovan, a local minority language (Russian, Ukrainian, Bulgarian, German or Yiddish) and English. The investigation of the linguistic landscape will help identify the dominant language(s) in the Moldovan capital, understand the relations between linguistic communities and the linguistic situation in Chișinău.
Қазіргі посткеңестік астананың лингвистикалық ландшафты (Кишинев, Молдова Республикасы мысалында)
Лингвистический ландшафт современной постсоветской столицы (на примере Кишинева, Республика Молдова)
Keywords: language situation; linguistic landscape; bi- and multilingualism; language policy; language ideology; post-Soviet countries; Chișinău; Moldova